Tumor in Vein and Liver Imaging Reporting and Data System (LI-RADS): Diagnostic Features, Pitfalls, Prognostic and Management Implications - Catania , R.; Fowler , K.; Elsayes , K.; Kono , Y.; Chupetlovska , K. (Seram, 2021)
Background Information: In patients with hepatocellular carcinoma (HCC), the presence of vascular invasion (tumor in vein - TIV) represents a poor prognostic indicator associated with decreased survival. Because a diagnosis of TIV precludes liver transplantation, knowledge of the imaging findings to differentiate between TIV and bland thrombus is key for proper patient management. In Liver Imaging Reporting and Data System (LI-RADS) v2018, LR-TIV is a distinct diagnostic category present in the CT/MRI and contrast-enhanced ultrasound (CEUS) algorithms. Educational Goals/Teaching Points: The purpose of our work is to review the imaging features of TIV on CT/MRI according to LI-RADS v2018 aimed to properly define LR-TIV and differentiate TIV from bland vascular thrombus. We will analyze diagnostic pitfalls that may confound the interpretation of CT and MRI in the diagnosis of LR-TIV and how to manage the indeterminate cases. Key Anatomic/Physiologic Issues and Imaging Findings/Techniques: According to LIRADS v2018, an observation is classified as LR-TIV only if it shows unequivocal enhancing soft tissue within the vein, regardless of visualization of parenchymal mass. For a confident diagnosis of LR-TIV, radiologists should be aware that risk of bland thrombus increases in patients with HCC and acute bland thrombus can expand the vein mimicking soft tissue, though it does not show enhancement. Moreover, thrombus may show hyperintensity on unenhanced T1-weighted images so that subtraction imaging needs to assess true enhancement. Peri-portal collaterals may mimic enhancement within the thrombus. Finally, diffuse HCC with necrotic thrombus may not show enhancement. While other features suggestive of TIV (i.e., occluded vein with ill-defined walls or restricted diffusion; occluded or obscured vein in contiguity with malignant parenchymal mass; heterogeneous vein enhancement not attributable to artifact) may be present, the observation cannot be classified as LR-TIV unless intravascular enhancing soft tissue is present. Finally, when enhancement on CT/MR is not unequivocal but images are suggestive of TIV, CEUS should be considered to detect early enhancement within the portal vein which is diagnostic of TIV, sometimes not evident on CT/MRI images. Prior versions of Liver Imaging Reporting and Data System (LI-RADS) classified the presence of tumor within lumen of vein as part of Category 5 criteria (LI-RADS5V). However, although HCC is the most common liver malignancy associated with TIV other tumors can have vascular invasion (e.g. intrahepatic cholangiocarcinoma). Conclusion: Because the diagnosis of tumor in vein drastically affects patient outcome and management only unequivocal features should be classified as LR-TIV. Knowledge of the most common pitfalls that will be encountered during routine clinical practice will allow radiologists to improve the diagnostic confidence and performance when using the LI-RADS algorithms for the interpretation of CT and MR imaging of the liver.